Proverbs in German Textbooks and their Equivalents in Indonesian - Iman Santoso; Sudarmaji Sudarmaji; Retna Endah Sri Mulyati; Sri Megawati (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. Lingual elements in the form of proverbs are often found in German textbooks. Proverbs can be a medium to understand the cultural background of the German language because it reflects the culture, values, and mindset of the speaking community. However, proverbs have not been widely studied in terms of their meaning and equivalent in  Indonesian. This research aims to examine the form of German proverbs in German textbooks and find the equivalent of Indonesian proverbs based on their meaning, figurative elements, and cultural backgrounds. This research is qualitative research with a literature study. The data source of this research is the German language textbooks used in universities in Indonesia. The data collected are German proverbs in phrases or sentences and analyzed morphologically and semantically to find their equivalent in Indonesian. The research instrument is the human instrument. Data collection is done by reading and note-taking techniques. The data’s validity is obtained by reading the data repeatedly and discussed in the Focus Group Discussion. The research findings showed that very few German proverbs have the same meaning and figurative elements as Indonesian. However, there are German proverbs that have the same meaning as Indonesian proverbs but have different figurative elements. In addition, there are German proverbs that do not have Indonesian equivalents. This finding confirms that people who speak German and Indonesian have different values and mindsets, although they also have the same perspective on certain realities.Keywords: Proverbs, German Textbook, The Meaning Of Proverbs, Figurative Elements